Synergistic effects of enzyme-microbe co-fermentation on the nutritional quality and digestibility of corn stalks - Wei, Jianwei; Sun, Meng; Wang, Chunqiang; Wang, Qingyue; Huang, Yingying; Ma, Wei; Wang, Ying (Frontiers in Microbiology, 2026)
IntroductionThis study aims to investigate the synergistic effects of combined probiotics and composite cellulase on the fermentation quality, nutritional value, and in vitro digestibility of corn stover.MethodsThe experiment was designed with different addition methods of combined probiotics and enzyme preparations to establish a control group (CON), a probiotics-only group (J), an enzyme-only group (M), and a combined enzyme-probiotics group (MJ), with three replicates per group. The dynamic changes in the fermentation quality of corn stover were measured at 7, 14, 21, and 28 days of mixed fermentation. Additionally, in vitro simulated rumen fermentation technology and principal component analysis were employed to evaluate the rumen fermentation characteristics of mixed silage at 7, 14, 21, 28 days and after 72 h, and the feasibility of its feeding was confirmed by slaughtering Yanbian yellow cattle following feeding trials to assess production performance.ResultsThe results showed that the MJ group exhibited the best fermentation quality compared to the CON, M, and J groups, with significantly reduced pH and ammonia nitrogen levels (p < 0.05), and significantly increased lactic acid and acetic acid contents (p < 0.05). Neutral detergent fiber, acid detergent fiber, and lignin significantly decreased (p < 0.05), while crude protein retention increased and dry matter degradation decreased. In vitro rumen fermentation further indicated that the MJ group had significantly higher DM digestibility compared to the CON group, and CP and fiber digestibility were significantly higher than in the CON, M, and J groups (p < 0.05), with total volatile fatty acid production significantly higher than in the CON, M, and J groups. Principal component analysis results showed that the MJ group remained closely associated with nutritional indicators over time. Feeding trials confirmed that the MJ group significantly improved the average daily gain, feed conversion efficiency, and slaughter performance of Yanbian yellow cattle compared to the CON group (p < 0.05).DiscussionThe results indicate that combined enzyme-probiotic treatment can synergistically enhance the feeding value of corn stover and the production performance of ruminants, providing a feasible technical pathway for the efficient utilization of agricultural waste.